FORMATION OF DISPERSE COPPER POWDER IN ANODIC SPACE IN SULFURIC ACID SOLUTION - Baeshov, A. B.; Makhanbetov, A. B.; Abduvaliyeva, U. A.; Kolesnikov, A. V. (Scientific Journal of Pedagogy and Economics, 2018)
The proposed article considers the dissolution of a copper electrode in the anodic polarization of a metal in the presence of a Ti (IV) ↔ Ti (III) catalyst system and the formation of an ultradisperse powder that have passed into a solution of copper (II) ions. Electrolysis was carried out under standard conditions in a sulfuric acid medium in an electrolyser with unshared spaces using DC. During the anodic polarization of copper electrodes copper ions (II) are formed. The copper (II) ions transferred to solution on the anode surface are reacted with titanium (III) ions to form a nanosized copper powder. As a result, a solution of colloidal copper is formed. The oxidized titanium (IV) ions diffuse in the direction of the cathode and are reduced to the trivalent state. It is shown that the ions of trivalent titanium reduce the ions of divalent copper formed at the anode to a nanoscale metal powder. Thus, in the course of electrolysis, titanium ions in the electrolyte form act as a continuous catalyst system. It is established that the stability formed in the anode space during electrolysis of solutions of colloidal copper varies with the concentration of titanium (III) ions